Collaborative risk mitigation through construction planning and scheduling : risk doesn't have to be a four letter word - Lana, Kay Coble (Emerald Publishing Limited, 2019)
In the complex, cash-strapped, high pressure world of modern construction, what do you do when something goes wrong? This work looks beyond the best-case scenario to give project managers, contractors, architects and engineers the tools to prepare effectively for the unexpected.